Model Intervensi Modifikasi Perilaku Self Esteem untuk Menurunkan Perilaku Berisiko Kesehatan pada Remaja - Veriza, Ervon; Razi, Pahrur; Rosalia, Elvin; Triana, Winda (Journal of Telenursing (JOTING), 2024)
This study aims to produce a behavioral modification intervention model of self-esteem and test its effectiveness in reducing adolescent health-risk behavior. The method used is a mixed method with a one-group pretest-posttest design. The results showed that most had self-esteem in the moderate category (73.70%), most did not recognize themselves as much as 60.26%, an increase in subject knowledge related to risky behavior after being educated was 21.79%, and 33.33% increased knowledge related to self-esteem. In conclusion, the behavioral modification intervention model of self-esteem (MIMSE) is effective in reducing health-risk behavior in adolescents at SMA 10 Kota Jambi. Keywords: Adolescent Behavior, Risky Behavior, Self Esteem